Whitewashed adobe : the rise of Los Angeles and the remaking of its Mexican past - Deverell, William, 1962- (Berkeley : University of California Press, 2004)
Chronicling the rise of Los Angeles through shifting ideas of race and ethnicity, William Deverell offers a unique perspective on how the city grew and changed. Whitewashed Adobe considers six different developments in the history of the city--including the cementing of the Los Angeles River, the outbreak of bubonic plague in 1924, and the evolution of America's largest brickyard in the 1920s.
Introduction: City of the future -- The unending Mexican war -- History on parade -- Remembereing a river -- The color of brickwork is brown -- Ethnic quarantine -- The drama of Los Angeles history -- Conclusion: Whitewashed adobe.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Mexican Americans -- California -- Los Angeles -- History; Los Angeles (Calif.) -- Ethnic relations -- History; Los Angeles (Calif.) -- History; Américains d'origine mexicaine -- Californie -- Los Angeles -- Histoire; HISTORY -- State & Local -- General; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Ethnic relations; Mexican Americans; California -- Los Angeles; History